American Cultural Patronage: The Limits of Privatization - Kevin V. MULCAHY; Laura CARSTEN (Revista Transilvană de Ştiinţe Administrative, 2003)
In sum, the economically-mixed and organizationally-pluralistic character of patronage in the United States belies the more dire predictions about the decline and fall of public culture. On the other hand, the role of philanthropy in supporting culture raises questions about the power accorded to private individuals and foundations in determining cultural policy. Similarly, the exigencies of earned income favors support for commercialized and commodified cultural offerings. Both developments present problems for the creation of an accountable and representative public culture.